CURRENT SITUATION OF PRESSURE ULCER IN ELDERLY PATIENTS WHO TREATED AT CENTRAL GERIATRIC HOSPITAL (Vietnam Journal of Community Medicine, 2022)
Objective: Describe current situation of pressure ulcer in Geriatric Patients who treat at Central Geriatric Hospital.Subjects and method research: A cross-sectional descriptive study was conducted on 250 elderly patients (aged 60 years and older) being treated at clinical departments of the Central Geriatric Hospital from November 2020 to August 2021. We used the Braden scale for pressure ulcer risk assessment and the NPUAP ulcer classification (2016).Result: The mean score for pressure ulcer risk according to the Braden scale was 16.50 points. Percentage of patients with scores distributed according to the criteria for assessing ulcer risk at level 1 point in terms of sensory, skin moisture, movement, self-rotation ability, nutrition, friction displacement; level of rated 1 point according above contents are: 2.0%, 0.4%, 23.2%, 16.0%, 4.8%, 12.8%, respectively. The rate of inpatients with pressure ulcers was 11.6%. The number of patients with only 1 ulcer accounted for the highest rate of 72.4%, having 2 ulcers was the second highest with 17.2% and having 3 ulcers was the lowest with 10.3%. Grade I, grade II, grade III, grade IV ulcers account for 27.5%, 22.5%, 32.5%, 17.5%, respectively. The position of ulceration is quite diverse, in order of appearance from most to least, the skin of sacrum & coccyx (37.5%), heel, buttock (15.0%), back (12.5%), shoulder blade, eye ankle, elbow (5%).Conclusion: The risk of pressure ulcers in the elderly treated in the hospital is high. The rate of ulcers was at 11.6%. Most of the patients had 1 ulcer site, the highest rate of ulcers in the coccygeal-sacral region was 37.5% and the rate of grade III ulcers was the highest, accounting for 32.5%.
Keywords: Pressure ulcers, elderly patient.